Copper(II) hydroxide/oxide-coated granular activated carbon for E. coli removal in water. Issue 2 (9th December 2022) - Li, Yali; Deletic, Ana; Henry, Rebekah; Zhang, Tong H.; McCarthy, David T.
Abstract: Low-cost granular filter media with hybrid bacterial adsorption and survival inhibition capability is highly desired for the development of a low-impact water filtration system. In addition to overall removal, a deeper understanding of the fate and transport behaviour of bacteria in such systems should also be obtained to guide system operation. In this study, copper(II) hydroxide nanoparticles-modified granular activated carbon via a single-step in situ coating was prepared and denoted as CuH-G. Copper release behaviour and Escherichia coli removal efficiency of CuH-G were studied in saturated columns as a function of salinity, flow rate, and hydraulic loading. Copper release decreased exponentially on increasing salinity in test water, which potentiates controlled copper release for desired bacteria inhibition efficiency. With an effective contact time of 3.7 min, CuH-G provided 3.0 and 1.6 log E. coli removal in test water of salinity 237 and 680 μS/cm, respectively. Copper leaching at these two salinities were 1.7 and 0.74 mg/l, respectively below the Australian Guidelines for Water Recycling: Augmentation of Drinking Water Supplies. Further study of E. coli transport and deposition behaviour in heat-treated CuH-G at 160 °C revealed that the observed removal was largely attributed to enhanced attachment during filtration and survival inhibition post filtration. HIGHLIGHTS: Stable copper hydroxide coating on porous media through simple in situ precipitation. Filters packed with the modified media removed bacteria at a fast flow rate. Copper release was controlled by salinity in test water and the below guideline value. Breakthrough curve modelling revealed attachment as the key process during filtration. Intermittent operation enabled adsorbed bacteria inactivated by locally released copper. Graphical Abstract